2017
DOI: 10.1016/j.jfoodeng.2017.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Purification of caprine oligosaccharides at pilot-scale

Abstract: The purification of caprine milk oligosaccharides (COS) by membrane filtration has been hampered by the low concentration of target COS and high concentration of lactose. In addition, their molecular weight proximity hinders the recovery of a COS fraction with high degree of purity and recovery yield. In this work, the recovery of a high purity COS concentrate was obtained by the optimization of an integrated approach including complete lactose hydrolysis, fermentation of the resulting monosaccharides and nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 35 publications
1
25
0
Order By: Relevance
“…Average lactose hydrolysis of 99.5, 99.6, and 99.8% were achieved at 1, 2, and 4 h, respectively. These results are in agreement with previously reported data for the hydrolysis of lactose in bovine whey permeate, for which nearly 100% of lactose hydrolysis was obtained at pH 4.5, temperature from 40 to 50 °C, and amount of enzyme ranging from 0.1 to 0.25% [10,12]. Rodriguez-Colinas et al, for example, showed that 0.1% ( v/v ) β-galactosidases from A. oryzae, at 40 °C, pH 6.7 was able to hydrolyze up to 96% lactose in 1.5 h, producing approximately 7.0 g/L of GOS in bovine whey [15].…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Average lactose hydrolysis of 99.5, 99.6, and 99.8% were achieved at 1, 2, and 4 h, respectively. These results are in agreement with previously reported data for the hydrolysis of lactose in bovine whey permeate, for which nearly 100% of lactose hydrolysis was obtained at pH 4.5, temperature from 40 to 50 °C, and amount of enzyme ranging from 0.1 to 0.25% [10,12]. Rodriguez-Colinas et al, for example, showed that 0.1% ( v/v ) β-galactosidases from A. oryzae, at 40 °C, pH 6.7 was able to hydrolyze up to 96% lactose in 1.5 h, producing approximately 7.0 g/L of GOS in bovine whey [15].…”
Section: Resultssupporting
confidence: 93%
“…The method relies on the integration of optimized processing conditions that favor maximum lactose hydrolysis and monosaccharide fermentation prior to oligosaccharides concentration by selective membrane filtration. This processing strategy has been recently applied for the recovery of caprine milk oligosaccharide (CMO) at pilot scale [10]. Recovery yields, however, were lower for goat milk (75%) compared to the ones obtained for bovine milk oligosaccharides (BMO) (95%).…”
Section: Introductionmentioning
confidence: 99%
“…Fourteen quantifiable oligosaccharides in goats milk-based infant formula were detectable by LC/MS, indicating that, structurally, GMO may represent an alternative to the human milk derivatives where breastfeeding is not possible. In addition, high purity and recovery of GMO consisting of 67.6% acidic and 34.4% neutral oligosaccharides have been demonstrated [36], indicating that potentially viable commercial production methods may be available in the not too distant future.…”
Section: Characterisation Of the Goat Milk Oligosaccharidesmentioning
confidence: 99%
“…However, during these treatments special care should be taken with the degradation of the bioactive OS and the occurrence of transgalactosylation reactions, which can give to new OS of different composition. Aquino et al (2017) stated that the-galactosidase from A. oryzae did not degrade the 3'sialyllactose, 6'sialyllactose and 6'sialyllactosamine, as previously assayed (De Moura Bell et al, 2016); however, the evolution of other OS and the potential production of new OS was not evaluated. As far as we know, the use of these treatments for the removal of lactose from goat colostrum, has not yet been carried out.…”
Section: Introductionmentioning
confidence: 93%
“…Some studies have evaluated the use commercial β-galactosidases (from Kluyveromyces lactis and/or from Aspergillus oryzae) to promote the formation of new GOS (allolactose, 6'galactobiose and 6'galactosyl-lactose) in reconstituted goat milk, however, the content and preservation of COS was not evaluated and these studies were not carried out for fractionation purposes (Zhu et al, 2018;Pruksasri and Supee, 2013). Only Aquino et al (2017) have recently proposed a novel approach based on the use of a -galactosidase from A. oryzae, followed by the treatment with S. cerevisiae and nanofiltration, for the purification at a large scale of oligosaccharides from goat milk. However, during these treatments special care should be taken with the degradation of the bioactive OS and the occurrence of transgalactosylation reactions, which can give to new OS of different composition.…”
Section: Introductionmentioning
confidence: 99%